Pengembangan Kurikulum Tahfidz Alquran; Studi Kasus Di MA Mambaul Ulum Tunjungmuli Purbalingga - Chully, Ardan By; Fajar, Abbas Sofwan Matlail (BULETIN ADALAH, 2023)
A dichotomous science paradigm must be changed. The curriculum emphasizes intelligence. Curriculum development will continue to innovate and assess students' talents and learning interests. The researcher proposed the thesis "Development of the Tahfidz Al-Qur'an Curriculum at MA Mamba'ul Ulum Tunjungmuli Purbalingga" with the following research subjects. Tahfidz al-Qur'an curriculum planning (2) Tahfidz al-Qur'an curriculum implementation (3) assessing tahfidz al-Qur'an curriculum. This case study research is qualitative. Participant observation, in-depth interviews, and documentation collect data. Flow model analysis was used for data reduction, display, and conclusion. (1) Creating the tahfidz al-Qur'an curriculum using curriculum planning, syllabus, and lesson plans. (2) The tahfidz al-Qur'an curriculum uses the Talaqi, Takrir, and Tasmi memory methods. (3) Formative and summative assessments evaluate curriculum (rewards to students, semester exams, student report cards).